Climate change intensification impacts and challenges of invasive species and adaptation measures in Eastern Ethiopia. Issue 1 (1st January 2021) - Bogale, Girma Asefa; Tolossa, Tasisa Temesgen
ABSTRACT: Invasive alien species (IAS) are the plant species whose introduction and spread outside of their natural past, present and threatens biological diversity. Prosofis juliflora impacts and driver pastoral vulnerability and agricultural lands where reduced biodiversity, loss of livestock forage and culturally valuable of indigenous species. The major adverse impacts of climate variability in Ethiopia include food insecurity arising from droughts and floods, outbreak of diseases, land degradation due to heavy rainfall. Climate change adaptation and mitigation prevent the introduction of new non-native species to minimize the possibility of future invasions. As compared to the current climatic condition, future climate prediction in 2070 will be highly suitable climate for the species by increasing by 73.3% and 80.0% under RCP4.5 and RCP8.5 scenario, respectively. Further reviews that consider different climate models with appropriate adaptation management options are necessary to better understand the impact of future invasive species in the study area.